The nature and history of the South Qilian orogenic belt: Constraints from compositions of rivers' sediments and their detrital zircon U–Pb geochronology, Lu‐Hf isotopic compositions. (22nd January 2019) - Kang, Huan; Chen, Yuelong; Li, Dapeng
Abstract : Detrital zircon U–Pb dating, Hf isotopic data, and Nd isotopic compositions of river sediments are used to constrain crustal evolution processes of their provenance in the South Qilian orogenic belt. The detrital zircons from the Yuka, Tataleng, and Bayinguole rivers range in age from Neoarchean (2, 772 Ma) to Permian (261 Ma), with age peaks at ca. 2.4 Ga, ca. 1.95 Ga, and ca. 0.45 Ga. Hf isotopic compositions of Paleoproterozoic, Pan‐African, and Caledonian zircon age groups display a wide range of ε Hf (t) values, suggesting diverse sources of host magma of the zircon grains. The basement formation of the South Qilian orogenic belt from depleted mantle occurred at two stages; ca. 3.1–2.5 Ga and ca. 2.0–1.6 Ga. Meanwhile, the Nd model ages of silt‐mud from the region are between 1.98 Ga and 2.27 Ga with an average value of 2.12 Ga. Our study indicates that the Qilian oceanic plate formed between the Qaidam and Alxa blocks from late Neoproterozoic to Silurian. The South Qilian orogenic belt is a product of the Qilian Ocean closure and subsequent collision between the Qaidam Block and central Qilian belt during Ordovician–Silurian times. Combining regional tectonothermal events with new results of river sediments suggests that rifting from a continent and opening of the Qilian Ocean occurred at ca. 780–520 Ma, subduction of the oceanic crust at ca. 520–440 Ma, ocean closure and continental subduction at ca. 440–420 Ma, exhumation of subducted crust at ca. 420–400 Ma, and orogenic collapse and extension at ca. 400–360 Ma.